A two-dimensional honeycomb coordination network based on fused triacontanuclear heterometallic Co12Mn18 wheels. Issue 34 (30th March 2015) - Liu, Jiang; Qu, Mei; Clérac, Rodolphe; Zhang, Xian Ming
Abstract : An unprecedented two-dimensional honeycomb paramagnetic network based on fused triacontanuclear heterometallic wheels of 3.4 nm, {[Co2 (Mn3 O)(N3 )2 (pic)6 (NO3 )] − }6, has been assembled. Abstract : An unprecedented two-dimensional honeycomb network based on fused triacontanuclear heterometallic wheels of 3.4 nm, {[Co2 (Mn3 O)(N3 )2 (pic)6 (NO3 )] − }6 (Hpic = picolinic acid), has been assembled. The hexagonal Co12 Mn18 wheel motif is composed of six oxo-centered Mn3 trinuclear and six Co2 dinuclear moieties acting as nodes and linkers, respectively. The paramagnetic properties of this compound observed down to 1.8 K result from the competition of Mn⋯Mn, Mn⋯Co and Co⋯Co interactions in combination with spin–orbit coupling and single-ion behavior of the Co(ii ) centers.